2021
DOI: 10.1038/s41467-021-24872-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying optimization of COVID-19 vaccine prioritization in the context of limited vaccination capacity

Abstract: Dynamically adapting the allocation of COVID-19 vaccines to the evolving epidemiological situation could be key to reduce COVID-19 burden. Here we developed a data-driven mechanistic model of SARS-CoV-2 transmission to explore optimal vaccine prioritization strategies in China. We found that a time-varying vaccination program (i.e., allocating vaccines to different target groups as the epidemic evolves) can be highly beneficial as it is capable of simultaneously achieving different objectives (e.g., minimizing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 38 publications
5
75
0
Order By: Relevance
“…These results are consistent with those of other model-based studies showing that the optimal vaccination strategy balancing direct and indirect protection against COVID-19 is highly determined by vaccine supply and efficacy [14,35,36] and vaccination of the most susceptible group is more efficient under a broad range of situations [37,38]. Our study adds two elements to previous approaches.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with those of other model-based studies showing that the optimal vaccination strategy balancing direct and indirect protection against COVID-19 is highly determined by vaccine supply and efficacy [14,35,36] and vaccination of the most susceptible group is more efficient under a broad range of situations [37,38]. Our study adds two elements to previous approaches.…”
Section: Discussionsupporting
confidence: 91%
“…As other models used to inform optimal vaccination roll-out [14,[35][36][37], our model assumes that individuals within a given group have on average the same number of contacts. More realistic models should consider heterogeneity in the number of contacts, since it has been shown that highly skewed contact distributions, with hubs (or, equivalent from a dynamic viewpoint, super-spreader individuals or events) have important effects in immunity thresholds [39] and in vaccination strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study also found that slower vaccination rates can lead to a prolonging of the COVID-19 pandemic, and a higher number of cases and deaths in the population [67]. Besides, to measure the optimal vaccine prioritisation of COVID-19 transmission, Han et al ( 2011) developed a data-driven mechanistic model in China [68]. In this model, they considered 17 age groups and divided the population into five compartments: the unvaccinated susceptible population (S); persons who received at least the first dose of vaccine but have yet to develop protection (V); persons who received the second dose of the vaccine but failed in protection (U); infectious individuals including asymptomatic and symptomatic infections (I); and recovered or immune individuals (R).…”
Section: Models With Age Structure and Vaccinationmentioning
confidence: 79%
“…Furthermore, this study recommended that, to minimise the number of deaths and ICU admissions, people over 65 years of age should be vaccinated before moving to other groups such as younger and middle-aged people. Finally, the early phase of high vaccination capacity is the key to achieving significant success of policy measures and implementations [68].…”
Section: Models With Age Structure and Vaccinationmentioning
confidence: 99%
“…Vaccination is one of the most effective measures in influenza control. Identifying and developing universal vaccines, as well as increasing the vaccination capacity ( 15 ) are of primary importance after influenza’s long-term disruptions to seasonal patterns. However, as the influenza season is approaching and a large part of a population has not been protected by vaccines, there is an increasing call for coordinated mitigation measures.…”
Section: Discussionmentioning
confidence: 99%